A hybrid solar/wind energy harvesting technique - Hou, Zehong (Nanyang Technological University, 2021)
Constituted of solar and wind energy, these are elements of clean energy that have been widely utilized to generate power by energy sectors. It is a disadvantage common to the wind and solar energy harvesting systems for having unpredictable performance because of weather and climatic changes, including radiation, ambient temperature, and wind speed. Thankfully, it is an issue that can be partially overcome. This is performed via integrating the two elements in right combination that creates a hybrid system, utilizing one’s elements pros to overcome its cons. In return, the difficulty of integrating the two resources results in a complex system; hence, making it tedious for an analysis. This report aims to present the design and development of the hybrid solar and wind energy harvesting system. The designed system is tested and simulated by software PSIM 9.1.4. This final year project focuses on designing a proper power converter circuit that can deliver a steady output current and voltage while the inputs change within the controlled range. The overall system consists of two parts, the main circuit and the control circuit. Simple power electronics like boost converter, DC to AC rectifier, AC to DC converter are used in the main circuit to generate desired three-phase output voltage before connecting to the microgrid. To have a nearly harmonics-free result, the MPPT, PI controller, abc/dq transformation are necessary for the control circuit.